PENGENDALI LPV POLYTOPIC UNTUK SISTEM DENGAN PARAMETER BERUBAH-UBAH - widowati, widowati (MATEMATIKA, 2007)
This paper proposes a polytopic LPV controller design for air craft lateral-directional dynamics. The state space matrices of the plant and the controller are represented by using polytopic linear parameter varying model. A controller synthesis is derived by an approach linear matrix inequalities evaluated at the 32 vertices of the polytopic model. From the simulation results, it can be show that a polytopic LPV controller can maintain the closed loop systems stability and performance. Â